Patient Radiation Doses in Interventional Cardiology Procedures - Pantos, Ioannis; Patatoukas, Georgios; Katritsis, Demosthenes; Efstathopoulos, Efstathios (Current cardiology reviews, 2009)
Interventional cardiology procedures result in substantial patient radiation doses due to prolonged fluoroscopy time and radiographic exposure. The procedures that are most frequently performed are coronary angiography, percutaneous coronary interventions, diagnostic electrophysiology studies and radiofrequency catheter ablation. Patient radiation dose in these procedures can be assessed either by measurements on a series of patients in real clinical practice or measurements using patient-equivalent phantoms. In this article we review the derived doses at non-pediatric patients from 72 relevant studies published during the last 22 years in international scientific literature. Published results indicate that patient radiation doses vary widely among the different interventional cardiology procedures but also among equivalent studies. Discrepancies of the derived results are patient-, procedure-, physician-, and fluoroscopic equipmentrelated. Nevertheless, interventional cardiology procedures can subject patients to considerable radiation doses. Efforts to minimize patient exposure should always be undertaken.